Rubber Ball Theory: An Elastic Model of Production Line Balancing and Its Impact on Supply Chain Performance - Nuri Kartini; Andri Hermawan; Mohd Razif Idris (Ann Publisher, 2026)
Background. Production line balancing is a key element in improving the capacity and stability of manufacturing systems, yet conventional practices often ignore the elastic relationship between production intervals, capacity, and resource structure. This research develops and formalizes Rubber Ball Theory, a theoretical approach that views production systems as elastic entities, where changes in one operational variable trigger compensatory responses in other variables. Aims. The objective of this research is to develop a mathematical model for interval-based production line balancing and analyze its impact on overall supply chain performance. Methods. The research methodology includes developing an interval-based line-balancing optimization model, integrating concepts of bottlenecks and elastic capacity planning, and conducting empirical testing through a manufacturing industry case study. The developed model minimizes the system interval as the primary control variable, accounting for capacity constraints, precedence relationships, and parallel machine configurations. Sensitivity analysis is performed to evaluate the system's response to changes in the target interval and the number of parallel resources. Result. The results show that emphasizing production intervals without adjusting structural capacity leads to system instability and bottleneck displacement, while an elastic approach based on Rubber Ball Theory can sustainably increase production capacity. Furthermore, this approach has been shown to improve the reliability, responsiveness, and efficiency of asset management in the supply chain and contribute to reducing the variability of production flows that trigger the bullwhip effect. Conclusion. The main contribution of this research is the provision of an integrated conceptual and mathematical framework linking production line balancing to supply chain performance through elastic management of production intervals. Implication. These findings provide theoretical and practical implications for designing more adaptive and sustainable production systems and capacity planning.